2017
DOI: 10.1590/1983-21252017v30n122rc
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Carcass Yield of Broilers Fed Increasing Levels of Sunflower Cake

Abstract: -This study aimed to evaluate the performance, carcass yield and intestinal morphometry of 1-to 21-day-old broiler chickens fed a diet containing increasing levels of sunflower cake, supplemented with or without an enzyme complex (EC). We used 1200 Cobb 500 birds, which were distributed in a completely randomized design in a 2x5 factorial scheme and five levels of sunflower cake inclusion (0, 5, 10, 15, and 20%) in diets supplemented or not with EC. Each treatment consisted of 5 replicates. Animals were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
7
1
1
Order By: Relevance
“…These results differ from those presented by Oliveira et al (2012) and Berwanger et al (2017), who observed a quadratic and a linear response of FI, respectively, after SC was included in the diet of broilers. However, those authors did not observe differences in FI between the SC-containing and the control treatments, similar to our findings.…”
Section: Production Performancecontrasting
confidence: 99%
See 1 more Smart Citation
“…These results differ from those presented by Oliveira et al (2012) and Berwanger et al (2017), who observed a quadratic and a linear response of FI, respectively, after SC was included in the diet of broilers. However, those authors did not observe differences in FI between the SC-containing and the control treatments, similar to our findings.…”
Section: Production Performancecontrasting
confidence: 99%
“…A distinct result was obtained by Oliveira et al (2012), who used increasing levels of SC up to 18% in the diet of broilers from 20 days of age and observed a linear decrease in FC. Our results corroborate those obtained by Costa Júnior et al (2015) and Berwanger et al (2017), who also did not observe a significant difference between birds fed diets containing SC and those fed the control treatment. Kalmendal et al (2011), however, reported that SC inclusion levels negatively affected the FC of broilers and recommended its inclusion up to 20%.…”
Section: Production Performancesupporting
confidence: 93%
“…The present results differ from those mentioned by Alagawany et al (2015), who did not observe significant effects of enzyme supplementation on the carcass characteristics of broilers fed sunflower meal. Berwanger et al (2017a) observed an increase in the yields of carcass, breast and drumsticks + thighs of broilers from 1 to 21 days of age that were fed enzyme-supplemented diets.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, it contains 23.80% ether extract, 0.72% calcium and 0.23% phosphorus (Berwanger et al 2014). However, its use in the feeding of poultry is limited due to the presence of fibre, phytate and chlorogenic acid, which are antinutritional factors that may compromise animal performance (Berwanger et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…O custo da alimentação dos animais pode chegar a cerca de 70% do valor total gasto na produção e é afetado pelo preço dos grãos e ingredientes, como a soja, fazendo com que o setor produtivo utilize fontes alternativas de alimentos com custos mais baixos (Berwanger et al, 2017).…”
Section: Introductionunclassified